91 METABOLIC AND CARDIAC MORPHO-FUNCTIONAL IMPROVEMENTS AFTER PCSK9 INHIBITORS ADMINISTRATION. (15th December 2022) - Clausi, Elvira; Miceli, Sofia; Cassano, Velia; Monaco, Vittoria; Armentaro, Giuseppe; Barbara, Keti; Condoleo, Valentino; Mancuso, Luana; Abramo, Francesca; Divino, Marcello; Alberto Pastura, Carlo; Perticone, Maria; et al.
Abstract: Aim: Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) is mainly produced by the liver, but it is also expressed in the heart. It plays a key role in cholesterol's metabolism. Recent studies suggest its possible role in cardiovascular (CV) diseases, promoting vascular inflammation, reactive oxygen species generation and atherosclerotic plaque formation. Global longitudinal strain (GLS), global myocardial work efficiency (GWE), reservoir (PALS) and pump (PACS) atrial function evaluated by speckle-tracking echocardiography are able to identify early subclinical ventricular and atrial myopathy. In the last years PCSK9 inhibitors have been introduced as innovative therapies for LDL plasma levels's reduction. The aim of our study was to investigate PCSK9 inhibitors's effects in secondary prevention's patients, equally assigned to Alirocumab or Evolocumab, who were statin-intolerant and/or not reaching the target of LDL-C <55 mg/dl using the maximum tolerated drugs' dosage at basal time and on semestral follow-up. Methods: We selected 30 patients (24 males and 6 females, mean age 66+8 years old), having several comorbidities: hypertension (97%), ICM (90%), CKD II-III stage (70%), polidistrectual atherosclerosis (67%), T2DM (50%), OSAS-COPD (20%), HF NYHA class II-III (20%). They underwent anthropometrical evaluation, biochemical analysis, oxidative stress markers assessment, liver elastography, and advanced echocardiogram at basal time and after six months of therapy. NOX-2 and Sp-selectin were assessed with ELISA sandwich. Data were analyzed with ANOVA, post-hoc Bonferroni's test and Chi-square. Linear correlation analysis was performed for variables whose variation were statistically significant. Results: As expected, lipid profile was greatly improved in all the subjects, reaching the target of LDL-C <55 mg/dl. We obtained a statistically significant reduction of total-cholesterol (32%, p<0, 0001), LDL-C (60%, p<0, 0001), TG (26%, p<0, 0001), TG/HDL ratio (27%, p<0, 0001); an increase of HDL-C (9%, p=0.001) and an improvement of glomerular filtrate evaluated by CKD-EPI (6%, p=0.007). We observed a statistically significant reduction of NOX-2 (27%, p<0, 0001) and Sp-selectin (36%, p<0, 0001). We obtained a statistically significant increase of PALS (16.9%, p<0, 0001), PACS (21%, p<0, 0001), GWE (9.7%, p<0, 0001), GLS (24%, p<0, 0001) and a statistically significant reduction of global wasted work (GWW; 15%, p<0, 0001), left atrial volume index (LAVI; 8%, p<0, 0001) and E/e' ratio (19%, p<0, 0001). The results of linear correlation analysis showed that PACS was significantly and inversely correlated with TG/HDL (r=-0.406, p=0.013) and NOX-2 (r=-0.416, p=0.011); PALS was significantly and inversely correlated with TG/HDL (r=-0.473, p=0.004) and NOX-2 (r=-0.435, p=0.008); E/e' was significantly and directly correlated with TG/HDL (r=0.654, p<0.0001) and NOX-2 (r=0.438, p=0.008); GWE was inversely correlated with NOX-2 (r=-0.422, p=0.01). Conclusions: Our study demonstrated for the first time that PCSK9 inhibitors are able to reduce left ventricular filling pressure, to increase atrial function (reservoir and pump), global cardiac performance (GLS and GWE), and eGFR after six months of treatment in high CV risk population. Our results could be partially explained with a reduction of oxidative stress markers, inflammation and cardio-lipotoxicity, probably linked to a modulation of PCSK9's heart expression and its toxic effect on CV and renal function. In addition, we observed a TG/HDL ratio's reduction, related to cardiometabolic and lipid profile improvement. Further studies are necessary to better investigate systemic benefit in a larger population with longer follow-up.